Citizenship, Sovereignty and Globalisation: Teaching International Law in the Post-Soviet Era - Anne Orford (Legal Education Review)
This article will deal with one aspect of feminist research and teaching about international law in the post-Soviet era: the need to think about international law ethically in ways that take account of how international lawyers are located in global networks of power. While international law has long been involved in “the organisation of power relations between white and ‘other’’’, it is particularly important in an era of global economic restructuring to study international law as a process that is implicated in the reproduction of inequality. As Andrea Rhodes-Little suggests: For feminists ... the further challenge thrown down by “other” women is that of how to resist those social practices which produce inequality and divide women against each other within a global context as well as in local contexts. In short, feminists search for ethical practices which are answerable for the power relations they produce. We also search for law which acknowledges its position in the organisation of power relations between women and women and between white and “other”. My argument about the need for “ethical” practices of teaching and research about international law, practices “which are answerable for the power relations they produce”, can be read as part of a larger debate about the need to reorient legal education and the production of knowledge about legality generally. It also draws on the work of those feminist and critical theorists who argue for the development of an ethical approach to education and to the production of knowledge in areas such as literary theory and cultural studies. The particular focus of this article is on the ways in which that approach to teaching international law can be explored through the inclusion, in international legal curricula, of material that questions the central notions of citizenship and sovereignty. In the first section, I will sketch some of the ways in which feminist theorists have attempted to ask a different set of questions about citizenship and sovereignty, by contesting the dominant conception of the citizen as a neutral disembodied individual, and by considering the implications of citizenship in a global context. Secondly, I will make some necessarily brief comments about teaching method, addressing the pedagogical issues that are raised when feminist, critical and postcolonial material is included in the law curriculum.